(untitled) (African Journal of Biomedical Research, 2023)
Cnidoscolus aconitifolius plant has been shown to have antinociceptive effect, but the underlying mechanisms are unknown. This study examined the antinociceptive mechanisms of action C. aconitifolius by probing the opiodergic, cholinergic, and adrenergic systems. Behavioural assessments of pain were done using the paw licking test caused by formalin, abdominal writhing induced by acetic acid and tail-flick tests. Methanol extract of C. aconitifolius (MECA) significantly reduces nociception in the paw licking ibduced by formalin and abdominal writhing induced by acetic acid but not tail flick test. Pretreatment with opoidergic and cholinergic blockers reversed these effects but not adrenergic blocker. MECA can be said to potentiate its antinociceptive effect by acting peripherally in the manner of opioidergic and cholinergic agents.